THE EFFECT OF TAXATION ON THE ACTIVITY OF ENTERPRISES - Kudiyarov Kishibay Ramatullayevich (Journal of Artificial Intelligence and Digital Economy, 2024)
This research examines the impact of taxation on the activities of enterprises. Theoretical and empirical approaches have been studied regarding the impact of taxation on the activities of enterprises. The issues of regulating the ratio of debt and private capital of enterprises by means of taxes are analyzed. As a result of the analysis, relevant conclusions were formed.